Programa de lectura literaria para el mejoramiento de la expresión oral en estudiantes del tercer grado de secundaria Institución Educativa Experimental UNAP, San Juan Bautista 2021 - Perdomo Ruiz, Jhony Lamberson (2024)
The purpose of this study is to evaluate the impact of the literary reading program on the development of oral expression in 3rd grade students year of the Experimental Educational Institution UNAP, San Juan Bautista 2021. It is an evaluative study with a quasi-experimental design, made up of a sample of 65 subjects, divided into two groups of 32 (experimental) and 33 (control), and the expression orally using a rubric. The findings indicated that the implementation of the literary reading program had a significant impact on the oral expression of the third grade high school students of the research sample, which led to the acceptance of this general hypothesis (p-value =0.000 <0.05).